Partnership plus: on the future of the NATO-Ukraine relationship - Kaim, Markus (2014)
Abstract: The aftermath of the political turmoil in February and the Russian annexation of Crimea in March leave Ukraine politically, economically and militarily weakened. A lack of cohesion within Ukrainian society and centrifugal forces in its regions only serve to complicate matters even more. The country will require foreign assistance, not least in guarding its territorial integrity and political sovereignty. Here there is an important role for NATO. It is currently unclear what thoughts should guide the Alliance as it realigns its relationship with Ukraine. (author's abstract)